2021
DOI: 10.3389/fcimb.2021.686035
|View full text |Cite
|
Sign up to set email alerts
|

CPI-637 as a Potential Bifunctional Latency-Reversing Agent That Targets Both the BRD4 and TIP60 Proteins

Abstract: The failure of highly active antiretroviral therapy (HAART) has been largely responsible for the existence of latent human immunodeficiency virus type 1 (HIV-1) reservoirs. The “shock and kill” strategy was confirmed to reactivate HIV-1 latent reservoirs by latency-reversing agents (LRAs) for accelerated HIV-1 clearance. However, a single LRA might be insufficient to induce HIV-1 reactivation from latency due to the complexity of the multiple signaling regulatory pathways that establish the HIV-1 latent reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, CPI-637-mediated TIP60 inhibition, in turn, stimulated BRD4 dissociation from the HIV-1 5'-LTR promoter, causing more effective binding of Tat protein with P-TEFb in comparison with the BRD4 inhibition alone. These data indicated that development of dual-target LRAs, including but not limited to BRD4/TIP60 inhibitors, might be a more promising remedy to effectively eliminate latent reservoirs [84].…”
Section: Bet Inhibitors (Betis)mentioning
confidence: 95%
“…Interestingly, CPI-637-mediated TIP60 inhibition, in turn, stimulated BRD4 dissociation from the HIV-1 5'-LTR promoter, causing more effective binding of Tat protein with P-TEFb in comparison with the BRD4 inhibition alone. These data indicated that development of dual-target LRAs, including but not limited to BRD4/TIP60 inhibitors, might be a more promising remedy to effectively eliminate latent reservoirs [84].…”
Section: Bet Inhibitors (Betis)mentioning
confidence: 95%